STRATEGI KOMUNIKASI KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI RIAU DALAM MENERAPKAN APLIKASI HAJI PINTAR - Fadhillah, M. Irfan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The Hajj pilgrimage is one of the pillars of Islam. The Ministry of Religious Affairs has launched a smartphone/mobile phone/android mobile application in the form of the Latest Generation of Smart Hajj in 2017. Efforts to develop the Smart Hajj application are always carried out by the Directorate General of PHU. However, these efforts are also not free from obstacles in the field, namely that the application is not yet widely known by hajj pilgrims in Indonesia. The objectives to be achieved in this study are to analyze and determine the communication strategy of the regional office of the Ministry of Religious Affairs of Riau Province in socializing the Smart Hajj mobile application, so that it is able to create an interactive virtual environment with an online basis so that it can support previous applications to attract more interest and make it easier for pilgrims to understand the material on the hajj and umrah pilgrimages. The study uses a qualitative method or is known as the term research subject. The results of this study are the communicator's strategy to know a lot of information about the Smart Hajj Application so that what is conveyed can be accounted for. The message conveyed is clear in a simple, fast and easy way in using the smart hajj application. The media used by the Ministry of Religious Affairs in implementing this smart hajj application is Press release Press Release. communicator, namely the Ministry of Religion of Riau Province in the implementation of the Hajj with the communicant, namely the entire community, both domestic and foreign, so that in communicating there is feedback. Keywords: Communication Strategy, Ministry of Religion, Smart Hajj